The addition of glycerol and sodium chloride to a hyperhydration protocol does not improve half-marathon time-trial performance in trained runners in warm conditions - Jardine, W. T.; Condo, D.; Aisbett, B.; Ross, M. L.; Burke, L. M.; Durkalec-Michalski, K.; Abbott, G.; Périard, J. D.; Carr, A. J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: We examined the effect of glycerol- and sodium-induced hyperhydration on a field-based half-marathon in warm conditions.